PENGARUH TATA KELOLA PERUSAHAAN DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Irwanto Handojo; Gabrielle; Dicky Supriatna (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to obtain the evidence regarding the influence of independent variables consisting of corporate governance, audit quality, and deffered tax expense on earnings management. Corporate governance as independent variable consists of audit committee size, managerial ownership, institutional ownership, and board size. The company used in this research are manufacturing company listed on the Indonesia Stock Exchange (IDX) from 2018 until 2020. The number of samples obtained is 480 data that matched the criteria of using the purposive sampling method. This research uses a multiple regression method. The novelty of this research is the addition of institutional ownership, board size, and deferred tax expense as independent variables. This research shows that audit committee size, managerial ownership, audit quality, institutional ownership, board size, and deferred tax expense have no effect on earnings management. Management has a chance and motivation to do earnings management in company. The action of earnings management in company can not be avoided.